Improving colloidal stability of silica nanoparticles when stored in responsive gel: application and toxicity study - Giovannini, Giorgia; Warncke, Paul; Fischer, Dagmar; Stranik, Ondrej; Hall, Andrew J.; Gubala, Vladimir (Nanotoxicology, 2018)
When silica nanoparticles (SiNP) are stored in aqueous solution, even for few hours, they have a tendency to form agglomerates and therefore adapt inhomogeneous structures. Here we present a very practical method to store SiNP in responsive hydrogel. We have confirmed that SiNP kept in the responsive hydrogel do not undergo through undesirable morphological changes and while in storage they maintain their excellent colloidal stability. The effect of SiNP hollowing (i.e. dissolution of the core of the particles that leaves empty cavity inside) was significantly inhibited in the hydrogel, which is a critical feature for any nano-medical applications (e.g. controlled drug release). To demonstrate the applicability of the hydrogel-storing concept within a biologically relevant context, in this work we have evaluated the toxicological effects of the responsive SiNP-gel formulation in a model in vitro (human cell line U87GM and hemocompatibility using red blood cells) and ex ovo (hen’s egg test) experiments. Particles stored in the gel as well as the pure gel did not affect the hemocompatibility (hemolysis and erythrocyte aggregation) up to a concentration of 100 µg/mL. Furthermore, systemic injections into the blood circulation of the chick area vasculosa confirmed the biocompatibility in a more complex biological environment. All evaluated toxicological values (hemorrhage, thrombosis, vascular lysis, and lethality) were comparable with the negative control, and no differences in toxicological response could be observed between the SiNP stored in hydrogel and the control nanoparticles stored in the solution.
CRIS-Team Scopus Importer:2020-10-13
Keywords: hemotoxicity; hen’ egg test; hydrogel; Nanoparticles; stability; storage; toxicity